2020
DOI: 10.31557/apjcp.2020.21.1.259
|View full text |Cite
|
Sign up to set email alerts
|

Survival Rates and Associated Factors of Colorectal Cancer Patients in Brunei Darussalam

Abstract: Background: Colorectal cancer (CRC) is the third most common cancer in both men and women. In most Asian countries, both the incidence and mortality rates of CRC are gradually increasing. In Brunei Darussalam, CRC ranks first and second in lifetime risk among men and women respectively. This study aims to report the overall survival rates and associated factors of CRC in Brunei Darussalam. Methods: This is a retrospective study examining CRC data for the period 2007 to 2017 retrieved from a population based ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 28 publications
0
31
1
Order By: Relevance
“…Within Asia, India was found to have the lowest survival rate of 31.2% for CRC patients while China has the highest with survival rate of 77% [27,28]. The survival rate of mCRC patients found within this study was 44.7% while the reported five year survival rate for CRC reported by Leong et al was 49.6% [5].There are more cases of male mCRC patients than female mCRC patients and a slightly shorter survival period of the male mCRC patients in our study ( Table 1). Prior research has indicated that gender contributes to survival outcomes and females were deemed to have better OS [29], possibly due to the protective effects of female sex hormones against CRC [30,31].…”
Section: Discussioncontrasting
confidence: 44%
See 3 more Smart Citations
“…Within Asia, India was found to have the lowest survival rate of 31.2% for CRC patients while China has the highest with survival rate of 77% [27,28]. The survival rate of mCRC patients found within this study was 44.7% while the reported five year survival rate for CRC reported by Leong et al was 49.6% [5].There are more cases of male mCRC patients than female mCRC patients and a slightly shorter survival period of the male mCRC patients in our study ( Table 1). Prior research has indicated that gender contributes to survival outcomes and females were deemed to have better OS [29], possibly due to the protective effects of female sex hormones against CRC [30,31].…”
Section: Discussioncontrasting
confidence: 44%
“…To our knowledge, this is the first study in Brunei Darussalam to analyse both the survival outcomes of metastatic CRC patients and those of mutant KRAS mCRC patients. Although a recent paper published on the survival rates and associated factors of CRC patients in Brunei Darussalam [5], investigation on survival outcomes of mutant KRAS mCRC patients and exploration on the various KRAS mutations in these patients are still in its infancy in this country. The reported median survival period was 57.0 months for CRC [5], while for mCRC patients, we estimated that the median survival period was 29.0 months.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding can be explained by the fact that our study population were young and cancers affecting females are commonly diagnosed younger than other cancers; breast (majority in the fourth and fifth decades) and gynecological cancer (i.e. cervical cancers between third and fifth decades) (Leong et al, 2019;Ong et al, 2018). Self-reported history of cancers in offspring or children having cancers only accounted for a small proportion of 0.1%, and this is not unexpected given the age demographic of our participants.…”
Section: Discussionmentioning
confidence: 88%